Developments in Chemistry Teacher International (CTI) - Sözbilir Mustafa (Chemistry Teacher International, 2025)
Chemistry Teacher International (CTI) is a peer-reviewed, open access journal supported by the Committee on Chemistry Education (CCE) of IUPAC and the Division of Chemical Education of EuChemS. The journal aims to serve as a platform for teachers at all levels, with a focus on research in chemistry education. The journal’s primary objective is to disseminate reports of good practice, research articles and reviews with a focus on the teaching and learning of chemistry. Since the publication of the inaugural issue in June 2019, the journal has published 20 issues to date. Five of these issues are dedicated, as special issues, to different topics considered important in chemistry education. We are delighted that CTI has been well-received by readers worldwide. Metrics on impact factors have placed CTI in Q2. The journal has a global reach, with authors contributing from 60 different countries, making it an international platform for scholarly dissemination.